Block Local to Unity and Continuous Record Asymptotics - H. Peter Boswijk (Tinbergen Institute, 2001)
This paper provides a continuous record interpretation of the block local to unity asymptotics proposed recentlyby Phillips, Moon and Xiao (2001). It also demonstrates that in the case of homogeneous dynamics and a fixednumber of blocks, the new asymptotic approximation coincides with the conventional local to unity asymptoticapproximation.
Keywords: 330; Zeitreihenanalyse; Theorie